2021
DOI: 10.1111/hex.13414
|View full text |Cite
|
Sign up to set email alerts
|

Demographics, health literacy and health locus of control beliefs of Australian women who take complementary medicine products during pregnancy and breastfeeding: A cross‐sectional, online, national survey

Abstract: Background Pregnant and breastfeeding women's use of complementary medicine products (CMPs) is common, and possibly associated with autonomous health care behaviours. However, the health literacy levels and health locus of control (HLOC) beliefs of women who use CMPs in pregnancy and lactation have not been previously assessed in a large Australian sample. Aim The aim of this study is to determine the health literacy levels and HLOC beliefs of women who use CMPs in pregnancy and lactation and determine the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 97 publications
0
3
1
Order By: Relevance
“…The majority of participants in our study received complementary supplements during pregnancy, which aligns with findings from studies in other countries that have shown significant usage of complementary supplements during pregnancy. [38][39][40][41] In comparison to earlier studies in the Kingdom of Saudi Arabia, 42 which reported that 81.8% of pregnant women received folic acid during antenatal care, our study indicated a notable advancement, with 88.13% of participants receiving folic acid. This suggests a rising level of awareness among pregnant Saudi women and a satisfactory provision of information by healthcare centers.…”
contrasting
confidence: 63%
“…The majority of participants in our study received complementary supplements during pregnancy, which aligns with findings from studies in other countries that have shown significant usage of complementary supplements during pregnancy. [38][39][40][41] In comparison to earlier studies in the Kingdom of Saudi Arabia, 42 which reported that 81.8% of pregnant women received folic acid during antenatal care, our study indicated a notable advancement, with 88.13% of participants receiving folic acid. This suggests a rising level of awareness among pregnant Saudi women and a satisfactory provision of information by healthcare centers.…”
contrasting
confidence: 63%
“…Among 111 studies, 102 studies were cross-sectional in design 27 61–161. Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of participants in our study received complementary supplements during pregnancy, which aligns with findings from studies in other countries that have shown significant usage of complementary supplements during pregnancy. 38–41 …”
Section: Discussionmentioning
confidence: 99%